Exploring Thermal Runaway: Role of Battery Chemistry and Testing Methodology - Sébastien Sallard; Oliver Nolte; Lorenz von Roemer; Brahim Soltani; Alexander Fandakov; Karsten Mueller; Maria Kalogirou; Marc Sens (World Electric Vehicle Journal)
One of the major concerns for battery electric vehicles (BEVs) is the occurrence of thermal runaway (TR), usually of a single cell, and its propagation to adjacent cells in a battery pack. To guarantee sufficient safety for the vehicle occupants, the TR mechanisms must be known and predictable. In this work, we compare thermal runaway scenarios using different initiation protocols (heat–wait–seek, constant heating, nail penetration) and battery chemistries (nickel manganese cobalt oxide, NMC; lithium iron phosphate, LFP; and sodium-ion batteries, SIB) with the cells in a fully charged state. Our goal is to specifically trigger a variety of different possible TR scenarios (internal failure, external hotspot, mechanical damage) with different types of chemistries to obtain reliable data that are subsequently employed for modeling and prediction of the phenomenon. The safety of the tested cells depending on their chemistry can be summarized as LFP > SIB >> NMC. The data of the TR experiments were used as the basis for high-fidelity modeling and predicting of TR phenomena in 3D. The models simulated reaction rates, represented by the typically employed Arrhenius approach. The effects of the investigated TR triggering methods and cell chemistries were represented with sufficient accuracy, enabling the application of the models for the simulation of thermal propagation in battery packs.